Active Carbon from Microwave Date Stones for Toxic Dye Removal: Setting the Design Capacity. Issue 9 (1st July 2020) - Hijab, Mouhammad S.; Parthasarathy, Prakash; Li, Puyu; Mackey, Hamish R.; Al-Ansari, Tareq; Mohammed, Rafie Rushdy; McKay, Gordon
Abstract: The widely used toxic dye malachite green (MG) poses a significant risk to human health, having a mutagenic effect. Waste date stones were used to produce microwave‐activated carbons and were applied to adsorb the highly toxic dye. The critically important task of selecting the correct design adsorption capacity for different effluent pollutant concentrations to meet effluent discharge limit standards is described and a novel design selection criteria approach is presented. Abstract : Activated carbons derived from waste raw date stone powder were employed to remove the toxic dye malachite green from water. The maximum adsorption capacity for each carbon was determined by the best fitting isotherm. A novel method is presented to predict the actual design capacity for a real wastewater treatment plant based on discharge standards showing that the adsorption capacity is not correct.